(untitled) (Journal of Educational Sciences, 2020)
The application of distance education technologies (DЕT) throughout the world is recognized as one of the most effective ways to achieve UNESCO’s goal of sustainable development – “ensure inclusive and equitable quality education and promote lifelong learning opportunities for all”. In our country, the problems of developing DЕT have become particularly acute due to the suspension of distance learning. The article attempts to address the contradiction existing in the field of the application of DЕT in higher education: on the one hand, there is a need for a large part of the population to receive education at a distance; on the other hand, a number of problems related to the implementation of distance education technologies in Kazakhstan’s higher education institutions remain unsolved: the legal and regulatory framework is not properly developed, content and software are not sufficiently prepared, and, most importantly, there is a lack of preparedness of professors and teachers for the implementation of DЕT. The leading methods of research were studying of normative-legal documents, sites and educational portals of higher education institutions, scientific articles and educational-methodical literature on DЕT problems, statistical data, questionnaires of teachers and specialists of higher education institutions in the field of DЕT, conversations with teachers and students, etc. Кey words: distance education technologies, higher education.